Sense of Community, Participation and Empowerment of citizens who wish to change their place of residence in Barranquilla, Colombia (Encuentros, 2025)
The sense of community is a key concept for community psychology and influences empowerment and participation at individual, organizational and community levels. These categories have the property of offering multiple alternatives to articulate processes of change and social transformation, based on the relationship that can be observed between people and social groups within the context in which they develop. The aim of the research that originates this article is getting to know the sense of community, level of empowerment and community participation that the inhabitants of a group of neighborhoods in the city of Barranquilla (north of Colombia) present, but with a special feature: manifesting their desire to change their place of residence. Methods: The study was carried out in 2019 with 1,334 people from Barranquilla (595 men, 739 women). For data collection the "Sense of Community Index 2 (SCI-2)" scales of Chavis and Acosta (2007), the "Empowerment Scale of Zimmerman and Zahniser" (1991) and the "Community Participation scale of Speer and Paterson" (2000) were used. Results: A sense of community, empowerment and participation was found that tends to be low or medium. In addition, a positive albeit slight correlation was found between these three variables. The Sense of community, empowerment and participation were recorded as low at a general level, but these present even lower levels in women and among those who live in rented places. Conclusions: It has been possible to establish that among the people who have openly expressed their interest in moving out of the place where they currently live, there is a low level of sense of community, empowerment, and community participation.
Keywords: Sense of community, empowerment, and participation, moving out of neighborhood, cross-sectional study.